2010
DOI: 10.1088/0960-1317/20/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Use of nanoporous columnar thin film in the wafer-level packaging of MEMS devices

Abstract: This paper presents a new packaging technology that uses a nanoporous columnar thin film to seal microelectromechanical system (MEMS) devices at the wafer level. In the proposed packaging process, the processing temperature is 350 • C. The process is relatively inexpensive compared to wafer level packaging processes, because the wafer-bonding step is eliminated and the die size is shrunk. In the suggested approach, a sputtered columnar thin film at room temperature forms vertical nanopores as etch holes, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Figure 1c shows the optical image of the final structure. [11,12] 2.2. Figure 1d to f represent scanning electron microscope (SEM) images inside the domeshaped structure (cross-sections near the center of the circular pattern).…”
Section: Proposed Process To Confine the Generated N 2 For Microcavitmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1c shows the optical image of the final structure. [11,12] 2.2. Figure 1d to f represent scanning electron microscope (SEM) images inside the domeshaped structure (cross-sections near the center of the circular pattern).…”
Section: Proposed Process To Confine the Generated N 2 For Microcavitmentioning
confidence: 99%
“…It can be observed that the fabricated microcavities have clear dome shapes. [12,16] One possible application for which the proposed technique might be useful is in preparing a transparent MEMS package of encapsulated N 2 . In the case of line patterns with no junction points such as "I" and "S" patterns, the final structures show homogeneous, smooth shapes along the lines.…”
Section: Applications Of the Proposed Processmentioning
confidence: 99%
“…To satisfy the market demand for MEMS devices, wafer-level packaging (WLP) has been widely developed by many research groups [2]. Among the WLP approaches in MEMS, thin-film encapsulation promises smaller area waste and lower cost [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To make matters worse, in the case of a micro-system with lateral etching holes, the process time for sacrificial layer etching is very long and depends on the lithography technology [6]. Also etching holes in the membrane can weaken the mechanical strength of the final system [2]. To avoid these problems, thin-film encapsulation with nano-porous material has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral feed-through establishes a metal line on the same surface of NMDS. [10][11][12][13][14] Therefore, the overall size of devices is larger than devices with the vertical feed-through. Furthermore, the fabrication process becomes complicated, which is unsuitable for batch processing.…”
Section: Introductionmentioning
confidence: 99%